Richard Grenville and the Lost Colony of Roanoke - Gabriel-Powell, Andrew 1959- (McFarland & Company, Inc., Publishers, 2016)
"England's first attempt to colonize America at Roanoke Island in 1585, more than 30 years before the Pilgrims set sail, has been the focus of numerous studies, fictional retellings and media interpretations. Drawing on newly discovered documents, recent archaeological finds and a close reading of contemporary writings, this book brings some fresh perspective to the Roanoke story"...